2002
DOI: 10.1128/jvi.76.11.5422-5434.2002
|View full text |Cite
|
Sign up to set email alerts
|

Transduction of Interphase Cells by Avian Sarcoma Virus

Abstract: It has been generally believed that oncoretroviruses are dependent on mitosis for efficient nuclear entry of viral DNA. We previously identified a nuclear localization signal in the integrase protein of an oncoretrovirus, avian sarcoma virus (ASV), suggesting an active import mechanism for the integrase-DNA complex (G. Kukolj, R. A. Katz, and A. M. Skalka, Gene 223:157-163, 1998). Here, we have evaluated the requirement for mitosis in nuclear import and integration of ASV DNA. Using a modified ASV encoding a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 54 publications
5
46
0
Order By: Relevance
“…The discovery that HIV-1 could complete early events in some non-cycling cells and that HIV-1 DNA could enter the nucleus through the NPC [Weinberg et al, 1991;Bukrinsky et al, 1992], appeared to distinguish HIV-1 from the prototype ''oncoretrovirus,'' MLV, which required mitosis. However, recent studies with ASV have demonstrated its capacity for mitosis-independent integration [Hatziioannou and Goff, 2001;Katz et al, 2002Katz et al, , 2003Greger et al, 2004], consistent with the earlier findings [Humphries et al, 1981]. Thus, mitosis-independent integration of viral DNA in non-cycling cells is not limited to HIV and lentiviruses.…”
Section: Historical Perspectives and Dogmasupporting
confidence: 85%
See 3 more Smart Citations
“…The discovery that HIV-1 could complete early events in some non-cycling cells and that HIV-1 DNA could enter the nucleus through the NPC [Weinberg et al, 1991;Bukrinsky et al, 1992], appeared to distinguish HIV-1 from the prototype ''oncoretrovirus,'' MLV, which required mitosis. However, recent studies with ASV have demonstrated its capacity for mitosis-independent integration [Hatziioannou and Goff, 2001;Katz et al, 2002Katz et al, , 2003Greger et al, 2004], consistent with the earlier findings [Humphries et al, 1981]. Thus, mitosis-independent integration of viral DNA in non-cycling cells is not limited to HIV and lentiviruses.…”
Section: Historical Perspectives and Dogmasupporting
confidence: 85%
“…There has been considerable focus on HIV NPCmediated import. However, as noted above, ASV can also infect some non-cycling cells [Hatziioannou and Goff, 2001;Katz et al, 2002;Greger et al, 2004] and may therefore also encode multiple signals that promote nuclear entry through the NPC.…”
Section: Nuclear Entrymentioning
confidence: 95%
See 2 more Smart Citations
“…Indeed, infecting G 1 /S-arrested cells with MLV resulted in the detection of two-LTR circle junctions 8 h after the cells were released and underwent a complete cycle (28). Recently, a comparison between retrovirus vectors demonstrated that aphidicolin-arrested cells could be infected by avian sarcoma virus but not by MLV vectors (20,25). In these studies, circular viral DNA molecules were looked for 16 to 24 h post viral infection as an indicator of PIC nuclear translocation and productive infection.…”
mentioning
confidence: 99%